The Planning and Implementation of Reasoning Instruction: Science Teachers’ Case - Sukardi, Rendi Restiana; Widodo, Ari; Sopandi, Wahyu (Journal of Engineering Education Transformations, 2025)
The study aims to investigate the planning and implementation differences of learning strategies that stimulate pupils’ reasoning skills on the topic of environmental pollution and also the reasons. This was a type of qualitative case study research involving five science teachers selected by purposive sampling technique. The instruments were content representation (CoRe) questions, lesson plan analysis formats, observation sheets, and unstructured interviews. The data were triangulated to get findings in detail. The results of the analysis showed that teachers had pedagogic content knowledge (PCK) about teaching reasoning skills. Unfortunately, it did not appear much in the lesson plan even in the implementation. There were differences between planning and implementation. The investigation through interviews showed that it was caused by the use of innovative teaching models that were less appropriate to pupils’ conditions and curriculum content in Indonesia. Teachers could not carry out reasoning instruction ideally. If the strategy was enforced, reasoning instruction would be not effective and it would take a long time. Teachers might have good PCK about reasoning skill development but they have to ensure that chosen learning strategies are appropriate to pupils’ condition and the curriculum content of Indonesia. Teachers have to adjust and even create reasoning instruction based on the condition of pupils and curriculum in Indonesia to achieve the learning goals well.